Universal Basic Income: Policy Options at National, State, and Local Levels - Howard, Michael (Maine Policy Review, 2018)
In this Commentary, Michael W. Howard addresses the questions: What is a basic income? Is it a desirable and feasible policy? And could such a policy be implemented on a state or local level?
Keywords: income; inequality; UBI; Maine